(untitled) (Heritage, 2023)
The reactualization of the subject of suffering in the Second World War/Holocaust is recognized as a key moment of memory through time which becomes the standard of our collective memory and our identity. In the musicological and theoretical-analytical context of cosideration of the current issues, a kind of psychological „replika“ was identified through three significant artistic achievements of Lazar Đorđević (1992), a representative of the new Serbian generation of composers, who is aware of the history of the Serbian people and their suffering, but also the layers of their emotional code in those moments, meticulously builts and sympathizes deeply. Unique works in us, IV Postcards from 1994 (2018), The 21st October (2020) and Letters from Semlin (2022), through authentic images, primordialy experienced through the vertical dimension of man in time, and on the traces of the original sourses, the inscriptions of the victims just before the moment of shooting, reflects a deep spectrum of the psychological shapes of the man of that time. The exceptional art of working with tembre, as a primary element of the composer’s musical expression in the mentioned works, is meticulously invoked and psychological though out profoundly. Looking deeply into the code of a man, his needs, desires, suffering, pain, fears, but also love, heroism, forgiveness, Đorđević represents the bridge – to the otherness carried over time, but also to the sameness of his vertical, spiritual dimension. With his creative poetics interwoven with the feature of a „man-seeker“, he reminds us of the importance of the memory, the significance of what is revived and relived. He calls to not forgetting the suffering of our people in the Second World War/Holocaust, underlying every „cry“ of a brave people, heroes fallen into eternity, as our cross, symbol and strenth to know to whome and where we belong, and where we are going next.